Clinical Significance of Thrombelastography Results in Patients with Lung Adenocarcinoma in Situ Complicated with Type 2 Diabetes. (July 2022) - Chen, Ke; Wang, Qiuping; Du, Xuan; Hu, Jingcheng; Niu, Lijuan; Zhou, Yingyi
To investigate the significance of thrombelastography (TEG) in patients who have lung adenocarcinoma in situ (LAIS) complicated with type 2 diabetes (T2D), 120 subjects were enrolled: 40 with LAIS, 40 with LAIS and T2D (LAIS + T2D), and 40 healthy controls (HCs). Correlation analysis was used to assess the relationships of TEG with indicators of T2D. The LAIS + T2D group had lower reaction time (R), rate of clot formation (K), estimated percentage of lysis (EPL), and lysis after 30 min (LY30), but higher maximum amplitude (MA), angle (α), and coagulation index (CI) than other group. Compared with the HC group, the LAIS group had lower R, K, EPL, and LY30, but higher MA, α, and CI. In LAIS + T2D group, R and LY30 had negatively correlations with fasting blood glucose (FBG) and triglycerides (TGs); α and MA had positive correlations with FBG and TG; K had negative correlations with FBG; EPL had negative correlations with FBG and low-density lipoprotein (LDL); and CI had positive correlations with FBG and LDL. TEG may be a useful indicator of blood coagulation dysfunction in these patients rather the healthy individuals.